The Language of Yellow Journalism - YUDIA YOSEF; OKTAVIANUS OKTAVIANUS; YEN POLISDA (STBA Prayoga Padang, 2015)
The aims of this article were to find the tendency of yellow journalism headline which often appears and to reveal the function of language in yellow journalismheadline. The data sources in this research were taken from English printed magazines and newspapers which were indicated as yellow journalism product.This research was a descriptive qualitative research. The research findings indicated that the form of headline was simple sentence. Simple sentence had some patterns: subject + verb, subject + verb + object, subject + verb + complement and subject + verb + object + complement. It was also found that a headline existed of phrase. The tendency of phrase were: noun phrase, verb phrase, and prepositional phrase. The headline had referential function , expressive function and social function.